INITIAL GEOMETRIC IMPERFECTIONS AKIBAT TEKUK SINGLE CURVATURE MOMENT PADA BALOK BAJA SEDERHANA - Yanuarini, Erlina; Setiawan, Yanuar; Swastika, Tri Widya (Politeknik Negeri Jakarta, 2020)
ABSTRACTSteel beams are susceptible to initial geometric imperfections due to improper fabrication and installation processes. Consequently, long steel beams without stiffening are prone to bending due to lateral torsion. The purpose of this study is to determine the effect of variations in the initial geometric imperfections of Single Curvature-Moment (SCM) on the moment, total displacement, displacement in the X direction (U1), displacement in the Y direction (U2), and twist. This study used an RH profile with a compact wing and body. The boundary condition used is a simple beam with an initial geometric imperfection due to single moment-curvature (SCM) bending. The variations used are the initial geometric imperfections values of SCM 0 mm (without initial geometric imperfections), SR5 (with initial geometric imperfections of 5 mm), and SR10 (with initial geometric imperfections of 10 mm). Initial geometric imperfections of SCM in steel beam decreased moment capacities up to more than 2% in elastic conditions and 12% in plastic states. This SR10 beam is also a beam that has a displacement of the X-axis (U1 = -203,960 mm), a displacement of the Y-axis (U2 = -255,615 mm), and the most significant twist (28,179 Â°).Keywords: buckle, initial geometric imperfections, Single Curvature-MomentABSTRAKBalok baja rentan mengalami initial geometric imperfections akibat proses pabrikasi maupun pemasangan yang kurang tepat. Sementara balok baja yang panjang tanpa pengaku rentan mengalami tekuk akibat torsi lateral. Tujuan dari penelitian ini adalah untuk menentukan dampak variasi besarnya initial geometric imperfections Single Curvature-Moment (SCM) terhadap momen, displacement total, displacement arah X (U1), displacement arah Y (U2), dan twist. Penelitian ini menggunakan profil RH dengan sayap dan badan yang kompak. Boundary condition yang digunakan adalah balok sederhana dengan initial geometric imperfections akibat tekuk single momen curvature (SCM). Variasi yang digunakan adalah besarnya nilai initial geometric imperfections SCM 0 mm (tanpa initial geometric imperfections), SR5 (dengan initial geometric imperfections 5 mm), dan SR10 (dengan initial geometric imperfections 10 mm). Dari hasil penelitian diketahui bahwa pada kondisi elastis, leleh, maupun plastis, balok dengan initial geometric imperfections SCM menunjukkan penurunan kapasistas momen mengalami penurunan hingga mencapai lebih dari 2% pada kondisi elastis dan 12% pada kondisi plastis. Balok SR10 juga merupakan balok yang memiliki displacement arah sumbu X (U1=-203,960 mm), displacement arah sumbuY(U2=-255,615 mm), dan twist yang paling paling besar (28,179Â°).Kata kunci: tekuk, initial geometric imperfections, Single Curvature Moment